Designing An Augmented Reality Teaching Framework for Mechanical Students at College Vocational in Malaysia - Abdul Jalil, Muhammad Zuhairi; Nizamuddin Razali ,; Mohd Erfy Ismail,; Faizal Amin Nur Yunus,; Debie Devisser Gerijih, (Journal of TVET and Technology Review, 2023)
With the impact of advanced technologies, people at young age have start using smartphones in their daily life. In the education sector, most researchers have started developing new teaching styles that can adapt to technology nowadays. This also including augmented reality technology that can be used as a teaching aid. However, there are no sufficient studies that analyze the suitable construct that can be formed as a framework as a reference for a mechanical teacher in College Vocational, Malaysia. In order to design a teaching framework to apply AR technology to the mechanical student the researcher performs a systematic literature review. This review analyses nine studies in the field. Based on the result that has been conducted, there are six constructs that have been explored: preparation, process, device, teaching approach, AR-type, and purpose. From this construct, several items has been extracted.